Problematyka nauczania umiejętności czytania w języku drugim/obcym w świetle najnowszych badań naukowych - Chodkiewicz, Halina (Neofilolog, 2009)
The present paper aims to provide a selective overview of major issues pertaining to L2/FL reading instruction with special attention to new research findings in the field. The problems chosen to focus on are: fluency and speed of reading, reading/vocabulary connections, the impact of discourse organization on the effectiveness of reading and strategy instruction. It is shown that empirical investigations carried out in recent years have shed more light on the many variables contributing to the ultimate success in L2 reading development and complex interrelationships between them. The discussion throughout the paper is illustrated with brief reports on selected studies and the problem of research methodology in the area is also emphasized. Implications for classroom instruction requiring L2 learners’ participation in a variety of reading tasks are suggested.